Of the Language of the Origins - Cavalcante Shuback, Marcia Sá; Aguirre, Beatriz (Íkala, Revista de Lenguaje y Cultura, 1999)
The ideas of identity, nation, culture and mother tongue according to Western tradition can all be related to the notion of space. However, nowadays as mankind experiences much uprooting, he must redefine such concepts in terms of spacelessness and life infinity. The language of beginnings, the mother tongue, allows mankind to reencounter his creative space and to stablish relationships.